Ideal Men and Dream Women: Computer Matchmaking in twen during the West German Sex Wave, 1967–1970*. - Cincotta, Natalie R (German History, 2022)
Between 1967 and 1970, the West German youth magazine twen embarked on an ambitious experiment to match young heterosexual pairs using computer programming. Named Rendezvous , the program emerged during a moment of particular promise and transformation in West German history. The so-called 'sex wave', an emphasis on self-discovery and the reconfiguration of social relationships, had produced both new possibilities and pressures for how young West Germans should 'get to know' each other and what they should find meaningful in their romantic relationships. Rendezvous promised to take the guesswork and disappointment out of finding an ideal partner through a rational, scientific assessment of habits, attitudes and desires. This article uses Rendezvous as a lens to examine early interactions between technology, media cultures and value change long before the internet age. Through an analysis of questionnaires, first-person accounts and photo reports, the article argues that Rendezvous evidences the centrality of mass media to the reorganization of courting and romance around notions of personal fulfillment and self-discovery during the late 1960s.